Cultural Differences, Economic Partnership and Its Implication for Diplomatic Effectiveness: A Study of Nigeria and China (2011-2024) - Olayinka Babatunde Adebogun; Daniel Rejoicing; Sunday Ogbonna; Timothy Ekeledirichukwu Onyejelem (Britain International for Academic Research (BIAR-Publisher), 2025)
This study explores how cultural differences between Nigeria and China have influenced diplomatic effectiveness from 2011-2024. Both countries have different cultural values that is shaped by religion or social structures and this affects diplomacy, communication and negotiation. This study also focuses on the key cultural dimensions and how they shape diplomatic relations and trade. This study also highlights the challenges such as: misunderstandings or misinterpretation due to the difference in culture or negotiation styles and this brings about trade imbalance. This study examines strategies like cultural exchange programs and training skills that helped bridge cultural gaps. this study adopts the Complex interdependence theory that was propounded by Robert Keohane and Joseph Nye in 1977. Also, data was collected using qualitative method 7 interviewees were Interviewed while data was also collected from secondary sources. The result of this study reviews that cultural difference has a great impact on economic partnership and it has an implication for diplomatic effectiveness and this difference hinders cooperation due to the difference in communication style. This study concludes by emphasizing that policy makers, diplomats and business leaders should develop a more effective strategies to strengthen bilateral ties and promote a sustainable development between Nigeria and China. This study recommends trade imbalance should be addressed and both countries should invest in cultural exchange programs and creating a clear and transparent agreement that protects the interest of both countries.